Hubungan Asupan Zat Besi (Fe) dan Vitamin C dengan Kadar Hemoglobin pada Siswi Kelas VIII SMP Negeri 3 Brebes - Canthia Mahameru Pradanti; Wulandari M; Hapsari Sulistya K (Universitas Muhammadiyah Semarang, 2015)
The main cause of anemia is iron deficiency. Other cause of anemia is an acute or chronic inflammation, parasitic infections and irregular. synthesis haemoglobin. Impact of anemia in young children is the increased morbidity and mortality, physical growth and brain inhibition, inhibition of motor development, mental and intelligence.This research is explanative research, with the sampling method is systematic random sampling. Sample takes as many as 58 of 136 students with a 10% reserve is 5,8 or 6 students, thus, the samples takewere 64 students rounded up to 65 student. To research hypothesis tested in this study with a statistical test non parametric, and correlation Rank Spearman to see the correlation between variables.There is the correlation between vitamin C intake with hemoglobin levels on grade 8 student SMP Negeri 3 Brebes (r = 0,551 and p value 0,000 < 0,05). There is the correlation between iron intake with hemoglobin levels on grade 8 student SMP Negeri 3 Brebes (r = 0,564 and p value 0,000 < 0,05)Keyword : Vitamin C intake, Iron Intake, Haemoglobin Level